2017
DOI: 10.1177/0047287517733555
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Self-Report and Psychophysiological Measures of Emotion in the Context of Tourism Advertising

Abstract: This study investigates the influence of emotional responses evoked by destination television advertisements on three common variables of interest when assessing tourism advertising effectiveness: attitude toward the advertisement, postexposure destination attitude and visit intention. In particular, this study used a combination of self-report and psychophysiological measures of emotion and explored the consistency between these two measurement techniques. A total of 101 participants were exposed to 18 existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 74 publications
(105 reference statements)
3
48
3
Order By: Relevance
“…This could utilise mixed methods to provide both subjective and objective analyses of residents' perceptions. For example, future research can use psycho-physiological tools such as electro-dermal analysis (EDA) or facial electromyography (EMG) (Li et al, 2017) to measure emotional responses coupled with self-report surveys.…”
Section: Methodological Directionsmentioning
confidence: 99%
“…This could utilise mixed methods to provide both subjective and objective analyses of residents' perceptions. For example, future research can use psycho-physiological tools such as electro-dermal analysis (EDA) or facial electromyography (EMG) (Li et al, 2017) to measure emotional responses coupled with self-report surveys.…”
Section: Methodological Directionsmentioning
confidence: 99%
“…Researchers in our field are beginning to see the potential in using physiological signals to measure the emotional component of experiences. In a lab setting, Li et al (2016Li et al ( , 2017 used facial EMG and SCR to measure emotional responses while study participants watched tourism destination advertisements. The researchers observed that physiological measures show reliable emotions that are consistent with post hoc interviews (Li et al, 2016) and further observed that the physiological effects of watching advertisements were weaker than self-reports of emotion, which suggests that self-reports may overestimate emotional responses (Li et al, 2017).…”
Section: Physiological Measures Of Emotionsmentioning
confidence: 99%
“…Other techniques such as storytelling (Schank 1990) Some studies attempt to compare and contrast verbal, nonverbal, and indirect qualitative emotion measures in tourism. Li et al (2018a) use self-report and psychophysiological techniques (facial EMG and skin conductance) to measure emotional responses to DMOs' advertisements. They show that self-report overestimates the effect of pleasure on advertising effectiveness.…”
Section: Verbal Nonverbal or Indirect Qualitative Emotion Measures?mentioning
confidence: 99%
“…Our article contributes to theoretical advancement by summarizing, integrating, and structuring extant knowledge across multiple literature streams. Theoretical and measurement issues relating to emotions appear in places but in piecemeal fashion in tourism (e.g., Kim and Fesenmaier 2015;Li et al 2018a). The present study brings together the fragmented literature, identify common grounds, and propose an enhanced conceptualization of emotion.…”
Section: Introductionmentioning
confidence: 99%